Healthcare access and cervical cancer awareness among Syrian refugee women in Türkiye: language, cultural, and economic challenges - Sabri Kurtay; Cuma Taşın (BMC Public Health)
Abstract Background The influx of Syrian refugees since 2012 has introduced demographic changes in Türkiye that face significant barriers to healthcare, particularly for women’s health and cervical cancer awareness. Studies indicate alarmingly low awareness, with only 4% of Syrian women aware of the smear test. Objective This study examines cervical cancer awareness among Syrian refugee women in Türkiye and assesses the impact of sociocultural factors—education level, healthcare access, and language proficiency—on healthcare utilization. Methods A sample of 409 Syrian refugee women aged 30–65 in Mersin was surveyed using a 21-item questionnaire, administered in Arabic, covering sociodemographic characteristics, obstetric history, Turkish proficiency, and cervical cancer awareness. Statistical analysis was performed with SPSS 22, with significance at p < 0.05. Results The mean participant age was 38.4 ± 3.70 years. Education and Turkish proficiency were significantly associated with cervical cancer awareness (p < 0.05). Only 8.6% knew HPV could cause cancer, and 26.9% knew appropriate screening intervals; low awareness was linked to reduced screening participation (p < 0.05). Of those not screened, 24.4% cited a lack of knowledge and 30% perceived low risk. Language barriers limited healthcare access for 22% of participants. Conclusions Cervical cancer awareness among Syrian refugee women in Türkiye is low, hindered by socioeconomic and cultural barriers. Addressing language barriers, adapting culturally appropriate awareness campaigns, and ensuring easier healthcare access could improve screening participation. Enhanced strategies and addressing funding shortfalls are essential for sustainable healthcare delivery and global cervical cancer prevention efforts.